Peran Kode Etik Profesi Akuntan dalam Pencegahan Fraud Audit pada Laporan Keuangan Koperasi - Pebrianti, Reska; Handayani, Monika (Indonesian Journal of Applied Accounting and Finance, 2024)
Fraud in financial reporting is one of the biggest threats to transparency and accountability of organizations, including cooperatives. This study aims to analyze the role of the code of ethics of the accounting profession in preventing audit fraud in the financial statements of the Sejahtera Bersama Savings and Loan Cooperative (KSP-SB) in 2023. A qualitative approach based on case studies was used to evaluate the application of the principles of the code of ethics, such as integrity, objectivity, and professionalism, which are relevant in preventing fraud. The results of the study indicate that consistent application of the code of ethics can minimize the risk of fraud, strengthen transparency, and increase public trust in financial reports. However, the study also found major challenges, such as weak internal supervision and lack of understanding of the code of ethics by cooperative managers. Therefore, this study recommends strengthening supervision, comprehensive code of ethics training, and stricter regulations to prevent similar cases from recurring in the future.